Cyber Laws Governing Online World in India - Bhavana (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Society includes institutions like family, school, religious organisations, polity. Polity makes rules and takes decisions for whole society. These laws create order in the society. Similarly, to regulate cyberspace, the online world and the related crimes, cyber laws are made. Covid 19 pandemic made us more connected and dependent to that online world. When the usage increased it also increased cybercrimes like hacking, cyber stalking, phishing, identity theft, cyber bullying, cyber terrorism, voyeurism. Data today is considered new oil. Government, private sector and individuals store lots of data virtually of the financial, personal and intellectual property nature and the one having access to it rules. Just like oil is a driver for any economy this position is now slowly taken by data. Hence the awareness about cyber laws and cyber security become much more crucial. Information technology act 2000 is a landmark statute that regulates cybercrimes also. Amendments to Indian penal code that defines crimes in India were made under the information technology act to include cybercrimes in that list. A subordinate legislation to this act has also been passed namely information technology rules 2021 to frame ethical code for social media platforms, digital media and OTT platforms. It is important that our population also have civic education and awareness regarding these legislative measures. Therefore, this paper aims to study cyber laws, cyber ethics and statues in place to prevent cybercrimes and build cyber security in India. It uses secondary sources for arriving at study results.